Distribution and Phenotype of Epstein-Barr Virus-Infected Cells in Inflammatory Bowel Disease - Spieker, Tilmann (American Society for Investigative Pathology, 2000)
Little is known about Epstein-Barr virus (EBV) infection of colon mucosa, particularly in inflammatory bowel diseases. Crohn’s disease and ulcerative colitis are thought to differ in T-helper lymphocyte composition and cytokine secretion patterns. Some of the implicated cytokines are growth factors for EBV-infected cells. We examined colon mucosa for differences in the distribution and phenotype of EBV-infected cells. Colon tissues with Crohn’s disease (n = 31) or ulcerative colitis (n = 25) and controls (n = 60) were characterized by in situ hybridization and immunohistology for six EBV gene products as indicators of latent and replicative EBV infection. The cells were additionally phenotyped by combined detection of the EBV transcripts and B- or T-cell antigens. B lymphocytes predominated as the site of latent EBV infection in the colon and were most numerous in ulcerative colitis. In active ulcerative colitis, EBV-positive lymphocytes accumulated under and within the epithelium and displayed evidence for replicative infection. The patterns of mucosal EBV gene expression indicate local impairment of virus-specific T-cell responses in active ulcerative colitis. Detection of EBV may help to discriminate between active ulcerative colitis and other inflammatory bowel diseases. Colon mucosa is a potential site of EBV replication and may be relevant for EBV transmission.